Environmental and legal aspects of sustainable development of the Arctic zone of the Russian Federation using the genomic technologies - Vedysheva N.O. (E3S Web of Conferences, 2020)
After analyzing the documents of the strategic planning of the Russian Federation, the state policy of the Russian Federation in the Arctic until 2035, the author makes an attempt to consider current legal problems in the field of environmental management and environmental protection in the region, ensuring the sustainable development of the Arctic zone of the Russian Federation. The article highlights the main threats and risks of ensuring the environmental safety, including when applying innovative, genomic technologies in the field of agriculture. In conclusion, a summary is made about the need to amend the legislation of the Russian Federation in terms of ensuring the environmental safety and sustainable development of the Arctic zone of the Russian Federation